Intravenous immunoglobulin in heart transplant recipients with mild to moderate hypogammaglobulinemia and infection. Issue 4 (6th January 2022) - Hoang, Johnny; Krisl, Jill; Moaddab, Mozhgon; Nguyen, Duc T.; Graviss, Edward A.; Hussain, Imad; Kassi, Mahwash; Yousefzai, Rayan; Kim, Ju; Trachtenberg, Barry; Bhimaraj, Arvind; Guha, Ashrith
Abstract: Background: Hypogammaglobulinemia (HGG) is a complication of solid organ transplantation leading to increased risk of infections. Intravenous immunoglobulin G (IVIG) replacement in patients with HGG may be able to reduce risk and morbidity associated with infection; however, there is scarce data about IVIG in mild to moderate HGG (IgG 400–700 mg/dl) and heart transplant recipients. Methods: A single center, retrospective study was performed in heart transplant recipients with mild (IgG 500–700 mg/dl) to moderate (IgG 400–499 mg/dl) HGG in the presence of an infection. Results: Forty‐two patients were included in this study; 19 patients (45.2%) received IVIG and 23 (54.8%) patients did not. Patients in the IVIG group received on average one dose of IVIG at 0.5 g/kg. No differences in incidence of new infection at 3 months (26.3% vs. 17.4%; P = .71) and 6 months (42.1% vs. 34.8%; P = .63) were observed between the IVIG and non‐IVIG groups. Infections based on mild or moderate HGG also had no differences at 3 and 6 months. Conclusion: Our findings suggest that a single infusion of IVIG in mild to moderate HGG may have little to no benefit in reducing incidence of new infections. Larger prospective studies are needed to confirm these findings.